Metal oxide nanotubes via electrodeposition for battery-electrochemical capacitor hybrid device - Yar, A. (Elsevier Ltd, 2022)
Charge accessibility in nanotube electrodes and consequent electrochemical properties exploitable for energy storage and sensing device is higher due to their dual surfaces than solid nanowires; however, their controlled growth is often challenging. This article demonstrates synthesis of metal nanowires of cobalt and nickel using a template-assisted electrodeposition technique and its transformation into cobalt oxide (Co3O4) and nickel oxide (NiO) nanotubes by controlled annealing. The materials are characterized for their phase, surface, and morphology. The Co3O4 nanotubes has a spinal-type crystal structure, an inner diameter of ~100 nm and wall thickness of ~220 nm with uniform micropores centered at ~21 nm, whereas NiO has a face centered cubic crystal structure, inner diameter ~90 nm and wall thickness ~330 nm with uniform micropores centered at ~21 nm. The electrochemical charge storability of the nanotubes is evaluated in an aqueous alkaline electrolyte (6 M KOH) using a three-electrode system measurement. The Co3O4 and the NiO nanotubes delivered discharge specific charges of ~324 and ~263 C gâ1, respectively, the difference charge storability is attributed to the surface and electrochemical properties. Further, a battery â electrochemical capacitor hybrid device is developed with desirable charge storage performance indicators using the Co3O4 nanotubes and reduced graphene oxide as positive electrode and negative electrode, respectively. This research thereby provides a method for developing scalable, reproducible, and efficient battery-electrochemical capacitor hybrid device using NiO and Co3O4 nanotubes. Â© 2021 Elsevier B.V.